Towards the Expansion of Energy Transition in Mali: Issues, Challenges, and Perspectives - Amidou BALLO; Daman-Guilé DIAWARA (International Journal of Scientific Research and Innovative Studies, 2025)
This study analyzes the dynamics and challenges of the energy transition in Mali, a country endowed with significant potential in renewable energy (solar, hydro, biomass). Access to reliable and sustainable energy remains a major issue for a large part of the population. The methodology relies on an economic and descriptive statistical analysis of data collected between 2010 and 2023. Sources include reports from the World Bank, the IEA, the Malian Ministry of Energy, as well as a critical review of energy policies. The study focuses on investments, installed capacities, electrification rates, and regional interconnection projects. The results reveal a significant expansion of renewable energy infrastructures between 2010 and 2023. The installed capacity of photovoltaic solar energy increased by 1,900%, while hydro capacity progressed by 180%, notably due to the Gouina dam. Energy storage capacities and hybrid power plants also experienced notable growth, with respective increases of 300% and 400%. This diversification of the energy mix has led to a 400% reduction in CO2 emissions related to electricity over the same period. However, major challenges persist. The national electrification rate, which rose from 32.5% to 50.6%, masks marked territorial inequalities (78% in urban areas compared to 18% in rural areas). Financial constraints, a lack of transportation and storage infrastructure remain significant barriers, as well as the need for increased geostrategic cooperation. To overcome these obstacles, we propose several solutions: strengthening research and public policies to attract private investments; developing new renewable energy power plants and hybrid systems; modernizing transportation networks using innovative technologies; and consolidating regional cooperation through the interconnection of electrical networks. This research underscores that the energy transition in Mali is both an opportunity for sustainable development and a challenge that requires an integrated approach to ensure socio-economic prosperity and climate resilience. Keywords: energy transition, renewable energy, access, climate resilience, energy policies. Received Date: August 21, 2025 Accepted Date: September 13, 2025 Published Date: October 01, 2025 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/465